Hypertension Associated with Coarctation of the Aorta Revisited: Case-Based Update from Experience of Three Children - Ali Baykan; Mustafa Argun; Abdullah Özyurt; Özge Pamukçu; Kazım Üzüm; Nazmi Narın (Case Reports in Pediatrics)
Coarctation of the aorta (CoA) can present with different clinical pictures depending on the severity of the narrowness in the coarcted aortic segment in an age range between newborn and adolescence. Sometimes, it can cause intracranial hemorrhage or infarction when diagnosis and treatment are delayed. The aim of this report is taking attention to CoA as a cause of systemic hypertension and is also emphasizing the differences of diagnostic approach for hypertension in children from adults. Two cases of hypertensive cerebral hemorrhage and one case of hypertensive cerebellar infarction associated with CoA are reported. These cases help us to pay attention to the possibility of CoA in adolescents with hypertensive stroke. We want to emphasize the importance of physical examination for evaluation of hypertension and to impress the diagnostic approach for secondary hypertension in children.